Identification of Risk Factors for Myopia Questionnaire in the Malay Language among Primary School Children in Malaysia - I, Nur Liyana; Kaur, Sharanjeet; MA, Saadah; Ac, Mahadir; O, Abdul Mutalib (IIUM Medical Journal Malaysia, 2018)
Introduction: This study aimed to develop a questionnaire in Malay language for the identification of risk factors for myopia among primary school children aged 10 to 12 years old in Malaysia. Materials and Methods: The study commenced in October 2012 till Julai 2013 in two main phases. The first phase was a pilot study for the construction of questionnaire items by literature review and discussion with the experts. A total of 103 parents of primary school children were randomly selected to test the comprehensibility of the preliminary questionnaire. The second phase was the actual study which involved parents of 353 primary school children , 132 were parents whose children were myopes and 221 parents whose children were nonmyopes. Results: Discussions with experts in human vision science identified 5 main domains and 71 items for the preliminary questionnaire. A total of 55 items were retained for the actual study phase in view of statistically good correlation (r = 0.4 and above). Predictive validity by chi-square test allowed 28 items to be retained because of significant association with myopia (p <0.05). The correlation coefficient of testretest reliability result was considerably good (r = 0.765) and the validity in 2 categories of risk for myopia showed highly significant predictive validity of the questionnaire (p = 0.000). Conclusion: The developed Malay language questionnaire has good reliability and validity to identify the risk factors for myopia among primary school children in Malaysia.